Família e prisão : uma análise interseccional sobre as relações familiares em uma instituição prisional masculina - Cúnico, Sabrina Daiana (2018)
This thesis aimed to understand the meanings attributed to family relationships, conjugality and paternity by men deprived of their liberty and their partners. Specific goals include: to perform a systematic review of the literature on fatherhood in the prison context; to discuss the challenges and possibilities of a qualitative fieldwork in Psychology; to understand if and how the meanings of paternity are transformed with the jail experience; to identify how men deprived of their freedom mean the concept of paternity and their own paternal condition; to understand which family models are constructed discursively and in practice by women who visit the partner in prison and to identify the relationship established between the prison institution, individuals deprived of their freedom and their relatives. In order to achieve the proposed goals, a qualitative, exploratory-descriptive and ethnographic based research was carried out. The collection of information occurred in two different moments. The first one comprised participant observations for three months in the Visiting Room, where family members undergo security and inspection procedures before joining the institution, as well as at the Children's Day and Christmas celebrations, organized by the warden management to the relatives of the prisoners. All observations were reported in a field diary. The second moment of collection included semi directed interviews with twelve men, fathers, who were deprived of their freedom for at least six months. All the information collected was analyzed in light of the Critical Discourse Analysis (CDA), and the results are presented and discussed in the five papers that compose the present thesis. Given the peculiarities of this research, it is observed that the results presented highlight the relevance that the affective relationships, among these the relationship between father and child, have space in the discussions that surround the Brazilian prison system, from the understanding that a father in prison is still a father and that maintaining affective bonds prior to incarceration brings benefits not only to the individual deprived of liberty, but also to their family members.